Heat and immunity: an experimental heat wave alters immune functions in three‐spined sticklebacks ( Gasterosteus aculeatus). (7th January 2014) - Dittmar, Janine; Janssen, Hannah; Kuske, Andra; Kurtz, Joachim; Scharsack, Jörn P.; Ardia, Daniel
Summary Global climate change is predicted to lead to increased temperatures and more extreme climatic events. This may influence host–parasite interactions, immunity and therefore the impact of infectious diseases on ecosystems. However, little is known about the effects of rising temperatures on immune defence, in particular in ectothermic animals, where the immune system is directly exposed to external temperature change. Fish are ideal models for studying the effect of temperature on immunity, because they are poikilothermic, but possess a complete vertebrate immune system with both innate and adaptive immunity. We used three‐spined sticklebacks ( Gasterosteus aculeatus) originating from a stream and a pond, whereby the latter supposedly were adapted to higher temperature variation. We studied the effect of increasing and decreasing temperatures and a simulated heat wave with subsequent recovery on body condition and immune parameters. We hypothesized that the immune system might be less active at low temperatures, but will be even more suppressed at temperatures towards the upper tolerable temperature range. Contrary to our expectation, we found innate and adaptive immune activity to be highest at a temperature as low as 13 °C. Exposure to a simulated heat wave induced long‐lasting immune disorders, in particular in a stickleback population that might be less adapted to temperature variation in its natural environment. The results show that the activity of the immune system of an ectothermic animal species is temperature dependent and suggest that heat waves associated with global warming may immunocompromise host species, thereby potentially facilitating the spread of infectious diseases.